2020
DOI: 10.2174/1570193x16666181228112313
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid Surfactant Combined (LASC) Catalyst as a Versatile Heterogeneous Catalyst in Various Organic Transformations

Abstract: Surfactant Aided Lewis Acids (LASCs) make an appearance as one of the efficient and substantial heterogeneous catalysts. Recently, various LASCs have been used as green and heterogeneous catalysts in organic synthesis due to their high water stability, recyclability, cost-effective nature and their ability to create stable colloidal dispersions. In the present review, we have discussed a variety of carbon-carbon bond forming, ring opening, addition and multi-component reactions for the synthesis of various bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It was reported that the amount of organic waste that is produced can be reduced tremendously by the use of 10 –2 to 10 –4 M surfactant solutions instead of 100% organic solvents. 10 Extensive efforts to realize the maximum effect of surfactants even under dilute conditions (especially catalytic amounts) resulted in the advent of designed nonionic surfactants 11 and surfactant-combined catalysts such as metal dodecylsulfates 12 or amphiphilic ligands. 13 In parallel, the use of dilute solutions of these surfactants has enabled multifarious catalytic reactions including asymmetric synthesis to be performed without the assistance of organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the amount of organic waste that is produced can be reduced tremendously by the use of 10 –2 to 10 –4 M surfactant solutions instead of 100% organic solvents. 10 Extensive efforts to realize the maximum effect of surfactants even under dilute conditions (especially catalytic amounts) resulted in the advent of designed nonionic surfactants 11 and surfactant-combined catalysts such as metal dodecylsulfates 12 or amphiphilic ligands. 13 In parallel, the use of dilute solutions of these surfactants has enabled multifarious catalytic reactions including asymmetric synthesis to be performed without the assistance of organic solvents.…”
Section: Introductionmentioning
confidence: 99%